2021
DOI: 10.1002/cpt.2402
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Modelling to Investigate the Impact of the Cytokine Storm on CYP3A Drug Pharmacokinetics in COVID‐19 Patients

Abstract: Patients with coronavirus disease 2019 (COVID‐19) may experience a cytokine storm with elevated interleukin‐6 (IL‐6) levels in response to severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). IL‐6 suppresses hepatic enzymes, including CYP3A; however, the effect on drug exposure and drug‐drug interaction magnitudes of the cytokine storm and resulting elevated IL‐6 levels have not been characterized in patients with COVID‐19. We used physiologically‐based pharmacokinetic (PBPK) modeling to simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Data for the in vitro suppression of CYP activity or mRNA from Dickmann et al (2011) have been used to successfully describe the clinical consequences of CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP3A4 and CYP3A5 suppression by IL-6 in PBPK models (Machavaram et al, 2013(Machavaram et al, , 2019Jiang et al, 2016;Xu et al,. 2015;Stader et al, 2021;Lenoir et al, 2021c). The former three models are designed to capture the therapeutic protein-drug interactions in patients who have chronically raised IL-6 levels (Machavaram et al, 2013(Machavaram et al, , 2019Jiang et al, 2016).…”
Section: Changes In Antipyrine Clearance In Subjects With Respiratory...mentioning
confidence: 99%
See 2 more Smart Citations
“…Data for the in vitro suppression of CYP activity or mRNA from Dickmann et al (2011) have been used to successfully describe the clinical consequences of CYP1A2, CYP2C9, CYP2C19, CYP2D6, CYP3A4 and CYP3A5 suppression by IL-6 in PBPK models (Machavaram et al, 2013(Machavaram et al, , 2019Jiang et al, 2016;Xu et al,. 2015;Stader et al, 2021;Lenoir et al, 2021c). The former three models are designed to capture the therapeutic protein-drug interactions in patients who have chronically raised IL-6 levels (Machavaram et al, 2013(Machavaram et al, , 2019Jiang et al, 2016).…”
Section: Changes In Antipyrine Clearance In Subjects With Respiratory...mentioning
confidence: 99%
“…In contrast, the models published in Xu et al (2015), Stader et al (2021) and Lenoir et al (2021) focus on transiently raised IL-6 levels. IL-6 levels increased rapidly to a mean peak of ~ 1600 pg/mL (60,000 pg/mL in the subject with the highest levels) at 6 h post blinatumomab administration and then decreased to baseline by 48 h (Xu et al, 2015).…”
Section: Pbpk Modeling Of Cytokine Suppression Of Cyp Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other target of curcumol, CYP3A4, is a member of the cytochrome P450 superfamily of enzymes. Many clinical trials suggested the importance of the cytochrome P450 system in the drug discovery of COVID-19 (40)(41)(42) because CYP3A metabolism is altered in patients with COVID-19 having increased cytokine release. In addition, an in vitro study of colon cancer stem cells demonstrated the contribution of CYP3A4 in the chemoresistance of colon cancer and its negative impact on disease-free survival in the patients (43).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, COVID-19 infection was associated with higher concentrations of lopinavir (a CYP3A4 substrate) than in patients with HIV 37,38 (Figure 2), and the related cytokine storm was predicted to increase the exposure to midazolam. 39 In that study, as in the other studies described below, midazolam was used as a prototypical CYP3A4 substrate and not as an anticonvulsant. Together, the findings from these works imply that systemic inflammation may be associated with phenoconversion of SMD metabolism toward generally poorer metabolizing phenotypes.…”
Section: Monoclonal Antibodies Can Affect the Metabolism Of Smallmolecule Drugsmentioning
confidence: 99%